The Church Renewal Movement in Ukraine: Based on the Materials of the Kharkiv “Tserkovna Hazeta” (1906) - Inna Horpynchenko (Київські історичні студії)
The article describes the church renewal movement, the emergence of which Ukraine at the beginning of the 20th century was a fully natural phenomenon due to the formation of initial liberal processes in society generally caused by the revolution of 1905–1907. It is shown that, not being national-liberation movement, the renewal movement was ideologically based in many respects on the principles of the functioning of the old Orthodox Church in Ukraine (Kyiv Metropolis), which was absorbed by the Moscow Patriarchate in 1686. The move was, in particular, about the independence of the church from the state, canon law, freedom of religion. As evidenced by the materials of the “Tserkovna Hazeta” (“Church Newspaper”), Kharkiv renewalists advocated the need for intra-church reforms in close connection with reforms of a general social nature. Among them were the following: shortening the working day and improving the working conditions of workers, overcoming the lack of land owned by peasants, granting civil rights and freedoms to all categories of the population, banning the death penalty. Rejecting the course of complete separation of the state from the church, the renewalists professed their harmony, the goal of which was declared to be the formation of a “Christian public”, and the means of its creation was to be non-violent “Christian politics”. The short-term existence of the church renewal movement is interpreted first due to the narrow social base of renewal at that time, and second to be a proof of the imperial Russian state’s inadmissibility of any forms of ecclesiastical and generally social liberal ideology.